The contributions of climate change and production area expansion to drought risk for maize in China over the last four decades. (22nd October 2020) - Song, Yanling; Tian, Jinfeng; Linderholm, Hans W.; Wang, Chunyi; Ou, Zhaorong; Chen, Deliang
Abstract: Maize is one of China's most important crops and is profoundly sensitive to drought. Using weather and county‐level maize yield data, the drought risk for maize in China was estimated for the period 1971–2010. The results show that drought risk has increased in China over the last 40 years, and that areas experiencing moderate to high drought risk have expanded, particularly in Northeast China. The main reasons for the observed changes are increased drought hazard associated with climate change, and increased exposure of maize to drought due to an expanded production area. Drought risk over all of China increased by 55% in the 2000s compared to the 1970s. While around 93% of the increase in drought risk in the maize production regions is due to increased drought exposure, 7% is attributable to climate change. In Northeast China alone, drought risk increased by 129% from the 1970s to the 2000s, which is the sum of an 86% increase caused by greater drought exposure, associated with expansion of the production area, and a 14% increase driven by climate change. The results indicate that the drought hazard has increased by around 13%, and drought risk has increased by 110% for each 1°C rise in annual mean temperature in Northeast China over the past 40 years. Maize yield losses have increased by around 4% per 1°C increase in annual mean temperature in this region. The sensitivity of maize to drought means that climate change is likely to have significant negative impact on future maize productivity, and China's export and import of maize is likely to be affected. Abstract : The drought risk had increased by 55% in 2000s compared to the 1970s for the whole China. 7% of the increased drought risk in the maize production regions was caused by climate change. Maize yield loss rate amounted to 19.4% for county‐level yield in drought years during 2001–2010, and it increased by 4.0% per 1°C warming in Northeast China. The increasing drought risk of maize from 1970s to 2000s in China.